2011
DOI: 10.1097/brs.0b013e3181f2d1ec
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Characteristics of rhBMP-2 In Vitro and in an In Vivo Rodent Model

Abstract: Swelling and inflammation after rhBMP-2 use are dose-dependent. Swelling may be due to direct contact as well as spread in the plane of access. The causes are a robust inflammatory reaction as well as sterile seroma and encapsulated hematoma formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
69
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 72 publications
(77 citation statements)
references
References 18 publications
5
69
1
1
Order By: Relevance
“…Exogenous BMP2 has been demonstrated to induce bone formation, but adverse effects including ectopic bone formation, osteolysis, and seroma formation have been reported [11,12]. Soft tissue inflammation was seen as early as 3 hours after subcutaneous BMP2 implantation in a rat model, an effect dependent on BMP2 dose [39,40]. We previously reported that exogenous BMP2 induced pro-inflammatory interleukin production by osteoblast-like cells on microstructured Ti surfaces in a TAB/TAK-dependent manner [13].…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous BMP2 has been demonstrated to induce bone formation, but adverse effects including ectopic bone formation, osteolysis, and seroma formation have been reported [11,12]. Soft tissue inflammation was seen as early as 3 hours after subcutaneous BMP2 implantation in a rat model, an effect dependent on BMP2 dose [39,40]. We previously reported that exogenous BMP2 induced pro-inflammatory interleukin production by osteoblast-like cells on microstructured Ti surfaces in a TAB/TAK-dependent manner [13].…”
Section: Discussionmentioning
confidence: 99%
“…In summary, this study accepted the hypothesis proposed and demonstrated the following: First, recombinant BGN devoid of posttranslational modifications specifically and predictably enhances BMP-2 function in vitro and in vivo; second, the bone formed by a low dose of BMP-2 combined with GST-BGN was well organized and mature when compared with that formed by a low or high dose of BMP-2 alone at 2 wk post-surgery; last, Smad pathway is consistently activated by BMP-2 and BGNassisted BMP-2 osteogenesis in vitro. The data suggest that by utilizing a BMP-2 functional effector such as recombinant BGN, smaller quantities of BMP-2 could be used to possibly minimize adverse side effects, such as ectopic bone formation and robust inflammation (Shields et al, 2006;Lee et al, 2011;Zara et al, 2011), and effectively regenerate craniofacial bone.…”
Section: Discussionmentioning
confidence: 99%
“…Following BMP-2/ACS implantation, the inflammatory response is characterized by the recruitment of both inflammatory cells and stem cells to the implantation site and by the presence of inflammatory cytokines in the sera, such as TNF-a, IL1b, and IL-6, in clinical patients as well as experimental animals [8,15,16]. Among these inflammatory cytokines, TNF-a and IL-1b have been reported to play an inhibitory role on BMP-2-induced osteogenic differentiation of BMSCs [17e21].…”
Section: Introductionmentioning
confidence: 99%